STRATEGI PENGEMBANGAN USAHA SUSU KUDA SUMBAWA DI KECAMATAN LENANGGUAR DAN MOYO UTARA KABUPATEN SUMBAWA NUSA TENGGARA BARAT - Nealma, Samuyus (Jurnal TAMBORA, 2017)
This study aims to analyze the factors strengths, weaknesses, opportunities and threats, as well as determining the strategic priorities that must be done in the development of Sumbawa horse milk in the district Lenanggguar and North Moyo Sumbawa of West Nusa Tenggara. The sampling technique is a technique Snowball Sampling by tracing where the respondent by asking a few people who are considered as key informants at the sites. Data collection techniques in this study is observational techniques, questionnaires, interviews and documentation. The analysis used in this development strategy include analysis matrix IFE (Internal Factor Evaluation) and EFE (External Factor Evaluation), a SWOT analysis, and analysis QSPM. The results of the study indicate that the main strength factor is the cheaper of price with the score 0.399. The main drawback is unlabeled BPOM with a score of 0.234. The main opportunities that can be utilized by businesses Sumbawa horse milk is a healthy and natural living trend as well as the benefits and efficacy of credits that have been known to the public with the same score of 0.344. The main threat is found at the level of inflation with a score of 0.272. Based on these results main strategy for Sumbawa horse milk business depelopment was improve the marketing strategy in a concentrated.